Transforming Islamic Education in the Digital Age: Challenges and Opportunities for the Young Generation - Muhammad Sanusi (CV. Creative Tugu Pena, 2024)
This article considers the manner in which Islamic education is undergoing a process of transformation, situated within the context of the evolving digital era. The advent of information and communication technology has brought about a series of challenges to Islamic education, including shifts in learning approaches, modes of material dissemination, and interactions between educators and learners. This research project aims to identify the challenges that are currently being faced in the implementation of Islamic education in the digital era, and to explore the potential opportunities that could be utilised in order to improve the overall quality of Islamic education. Through a comprehensive literature review and a detailed case analysis, the article ultimately concludes that, despite the challenges that are currently being faced, the digital era also provides a number of significant opportunities for innovation in teaching and learning methods that could potentially serve to strengthen the understanding and practice of Islamic teachings among the younger generation. This article considers the manner in which Islamic education is undergoing a process of transformation, situated within the context of the evolving digital era. The advent of information and communication technology has brought about a series of challenges to Islamic education, including shifts in learning approaches, modes of material dissemination, and interactions between educators and learners. This research project aims to identify the challenges that are currently being faced in the implementation of Islamic education in the digital era, and to explore the potential opportunities that could be utilised in order to improve the overall quality of Islamic education. Through a comprehensive literature review and a detailed case analysis, the article ultimately concludes that, despite the challenges that are currently being faced, the digital era also provides a number of significant opportunities for innovation in teaching and learning methods that could potentially serve to strengthen the understanding and practice of Islamic teachings among the younger generation.